2015
DOI: 10.1111/pim.12180
|View full text |Cite
|
Sign up to set email alerts
|

Immunology in wild nonmodel rodents: an ecological context for studies of health and disease

Abstract: Transcriptomic methods are set to revolutionize the study of the immune system in naturally occurring nonmodel organisms. With this in mind, the present article focuses on ways in which the use of 'nonmodel' rodents (not the familiar laboratory species) can advance studies into the classical, but ever relevant, epidemiologic triad of immune defence, infectious disease and environment. For example, naturally occurring rodents are an interesting system in which to study the environmental stimuli that drive the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 100 publications
0
27
0
Order By: Relevance
“…Multiscale studies of infectious diseases in wild populations can yield discoveries in applied and basic aspects of infectious disease biology, and build upon laboratory-based studies. For example, foundational ecoimmunology work in wild rodents has uncovered dramatic differences in immune function between laboratory mice and their wild congeners [5,6,10], demonstrating that simply giving disease a real-world environmental context can shift findings dramatically. Building upon this work, putative candidate genes for tolerance have been identified in wild rodents and tied to gene expression-based biomarkers, connecting animal-level disease to fine-scale gene expression patterns [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Multiscale studies of infectious diseases in wild populations can yield discoveries in applied and basic aspects of infectious disease biology, and build upon laboratory-based studies. For example, foundational ecoimmunology work in wild rodents has uncovered dramatic differences in immune function between laboratory mice and their wild congeners [5,6,10], demonstrating that simply giving disease a real-world environmental context can shift findings dramatically. Building upon this work, putative candidate genes for tolerance have been identified in wild rodents and tied to gene expression-based biomarkers, connecting animal-level disease to fine-scale gene expression patterns [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus inbred mouse lines, unlike humans and domesticated animals, are genetically homogenous [ 10 ] and even outbred stocks may show restricted genetic variability [ 11 ]. Furthermore laboratory rodents are maintained under extremely benign and pathogen-free conditions, whereas humans and domesticated animals still encounter many infections and environmental insults, albeit that these are different to those occurring in nature [ 12 ]. Moreover, the singular genealogies of laboratory rodents make them difficult to compare directly with wild counterparts, even leaving the effects of inbreeding aside.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our work broadens knowledge of the immune system of the bank vole–a well-established species in ecological and evolutionary research, and an emerging, non-murine model in the field of eco-immunology and studies of zoonosis 66 , 67 . We showed that an informative analysis of an individual TCR repertoire is possible with partial information on the genomic composition of the TCR locus (e.g., we did not have full sequences of genomic segments prior to somatic recombination and had only provisional assignment to the actual loci for V and J segments).…”
Section: Discussionmentioning
confidence: 82%